The Cambridge introduction to travel writing - Youngs, Tim, 1961- (Cambridge University Press, 2013)
Critics have long struggled to find a suitable category for travelogues. From its ancient origins to the present day, the travel narrative has borrowed elements from various genres - from epic poetry to literary reportage - in order to evoke distant cultures and exotic locales, and sometimes those closer to hand. Tim Youngs argues in this lucid and detailed Introduction that travel writing redefines the myriad genres it comprises and is best understood on its own terms. To this end, Youngs surveys some of the most celebrated travel literature from the medieval period until the present, exploring themes such as the quest motif, the traveler's inner journey, postcolonial travel and issues of gender and sexuality. The text culminates in a chapter on twenty-first-century travel writing and offers predictions about future trends in the genre, making this Introduction an ideal guide for today's students, teachers and travel writing enthusiasts.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Travelers' writings, English -- History and criticism.; Travelers' writings, American -- History and criticism.; Travelers' writings -- History and criticism.; Travel in literature.; Travel writing -- History.; Voyages and travels -- Historiography.